Mass spectrometric analysis of host cell proteins interacting with dengue virus nonstructural protein 1 in dengue virus-infected HepG2 cells - Thanyaporn Dechtawewat (2018)
© 2016 Elsevier B.V. Dengue virus (DENV) infection is a leading cause of the mosquito-borne infectious diseases that affect humans worldwide. Virus–host interactions appear to play significant roles in DENV replication and the pathogenesis of DENV infection. Nonstructural protein 1 (NS1) of DENV is likely involved in these processes; however, its associations with host cell proteins in DENV infection remain unclear. In this study, we used a combination of techniques (immunoprecipitation, in-solution trypsin digestion, and LC–MS/MS) to identify the host cell proteins that interact with cell-associated NS1 in an in vitro model of DENV infection in the human hepatocyte HepG2 cell line. Thirty-six novel host cell proteins were identified as potential DENV NS1-interacting partners. A large number of these proteins had characteristic binding or catalytic activities, and were involved in cellular metabolism. Coimmunoprecipitation and colocalization assays confirmed the interactions of DENV NS1 and human NIMA-related kinase 2 (NEK2), thousand and one amino acid protein kinase 1 (TAO1), and component of oligomeric Golgi complex 1 (COG1) proteins in virus-infected cells. This study reports a novel set of DENV NS1-interacting host cell proteins in the HepG2 cell line and proposes possible roles for human NEK2, TAO1, and COG1 in DENV infection.